Social Origin and Graduation Age: A Cohort Comparison of Danish University Students. Issue 2 (3rd March 2016) - Klausen, Trond Beldo
Abstract : This paper investigates whether social origin has an impact on graduation age among university students. A large number of social background factors are applied on a large data set of 4 successive cohorts of Danish university graduates born 1960–1975. These are cohorts for whom university attendance increased steeply. Contrary to recent findings on educational attainment in Scandinavia, the analyses show that the economic capital of the family of origin plays a somewhat greater role than does the cultural capital of the family of origin for getting their offspring through higher education on schedule. The impact of cultural capital decreases across cohorts, but the impact of economic capital is fairly constant.